Kualitas Vermikompos Limbah Blotong Tebu (Saccharum oficinarum L.) dengan Variasi Jenis Cacing - Dwi Anggraeni Susanti; Purwadi; Siswanto (Jurnal Biotek, 2022)
lotong is a sediment of dirty sap obtained from a sugar factory's sap purification process. The continuous accumulation of waste can cause environmental pollution. Blotong waste has the potential to be used as organic fertilizer using the vermicomposting method (composting with the help of earthworms). Blotong contains nitrogen, P2O5, humic acid, and other nutrients that can be used to fertilize and improve the structure of the soil. This study aims to determine the effect of the type of worm on the speed of decomposition of blotong waste and to determine the quality of vermicompost according to SNI 261-2019 regarding the specification of solid organic fertilizer. This study was structured using a one-factor completely randomized design (CRD) with three replications conducted in series. The series of observations were 2 MSP, 3 MSP, and 4 MSP (Week After Giving). The research factor was the type of worm consisting of Eisenia foetida (C1), Eudrilus eugeniae (C2), and Lumbricus sp. (C3). This research is destructive (not returned for further observations). The results showed that the compost with Eisenia foetida had a better content, namely C-organic (35.84%), pH (7.26), N-total (2.36%), and C/N ratio (15.19). The highest increase in worm mass was found in the type of worm Eisenia foetida, which had an increase of 7.11 g. Based on these results, sugarcane waste fertilizer meets the requirements of SNI No. 261/2019.